DAMPAK PANDEMI COVID 19 TERHADAP DUNIA PENDIDIKAN - Mungky Hendriyani; Ni Made Artini; Tatyana Tatyana (ITB Swadharma, 2021)
Corona virus 2019 (COVID-19) is an infectious disease caused by acute corona virus 2 respiratory syndrome (SARS-CoV-2). So that the impact on the community and students can not meet directly on campus or in public places. Based on Nielsen's research entitled